ACTIVE ISLAMIC-LINGUISTIC UNITS IN THE UZBEK LITERARY NORM: A LINGUISTIC AND CULTURAL PERSPECTIVE - Dilshodbek Yuldashovich Khakimov (Bright Mind Publishing, 2025)
This study explores the active role of Islamic linguistic units in shaping the Uzbek literary norm through a linguistic and cultural lens. Rooted in centuries of Islamic civilization, the Uzbek literary language incorporates Arabic-origin lexemes such as niyat, taqwa, duo, sabr, ajal, and halol, which have undergone deep phonetic, semantic, and symbolic adaptation. Drawing upon classical and modern texts—from Alisher Navoi and Babur to Oripov and Vohidov—the research examines how these units function as instruments of moral, aesthetic, and philosophical expression. Through qualitative-descriptive, semantic, and contextual analyses, the study identifies three main functions of Islamic linguistic elements: (1) linguistic adaptation, reflecting grammatical integration and lexical productivity; (2) literary-symbolic expression, where Qur’anic and hadithic concepts become aesthetic vehicles for metaphysical thought; and (3) ethical-educational influence, reinforcing Islamic virtues within literary discourse. Findings reveal that Islamic-origin lexemes serve not merely as lexical borrowings but as enduring cultural codes that embody moral values and collective identity. Consequently, they sustain the spiritual and ethical continuity of Uzbek literature while enriching its expressive potential. The paper concludes that Islamic linguistic heritage remains a living moral force, bridging tradition and modernity in the evolution of the Uzbek literary language.
Keywords: Islamic linguistics; Uzbek literature; Arabic-origin lexemes; cultural semantics; moral discourse; Alisher Navoi; linguistic adaptation; Islamic worldview; religious vocabulary; literary symbolism.